The persistence of institutions - Jöst, Frank; Fischer, Beate (Sustainability and the art of long term thinking, 2017)
When attempting to examine policy processes in terms of their sustainability and with a view to actively shaping them, it is particularly important to consider institutions as a category of immaterial stocks. As detailed in the previous chapter, it is possible to gain considerable insight into the immaterial circumstances of human behaviour by analysing institutions as stocks. It is especially important here to understand the development of institutions over time, that is, their persistence through time, their stability, their inertia and their potential resistance to changes as well as their volatility. Understanding the temporality of institutions is a crucial precondition for being able to intervene actively in order to shape and to manage them - although it should be noted that interventions in any institutional structure often need to be planned over the very long term.
Gesehen am 28.08.2024